After the Wildfire : Ten Years of Recovery from the Willow Fire - Alcock, John, 1942- (Book collections on Project MUSE., 2017)
"Very few people have ever returned again and again to the site of a natural but disastrous wildfire. John Alcock is such a returnee who recorded the aftermath of the Willow Fire, which burned a large part of the Mazatzal Mountains in central Arizona in the summer of 2004. His book on the subject, Wildfire on the Mountain, describes what happened to the lower reaches of the Mazatzals in the following decade or so. By walking along the South Fork of Deer Creek in all seasons as the years passed, he was rewarded by seeing a remarkable recovery of plant life, which in turn fostered an equally satisfying return of animals to the area ranging from small insects to large mammals. In this book you will find an accessible account of what is known about the response of chaparral plants to fire and the creatures that re-inhabit these plants as they come back from a ferocious blaze. In a series of short chapters, the author introduces us to what he observed on his many walks along the South Fork where he saw the great spreadwing damselfly, the western meadowlark, the reintroduced elk, and many more animals. The questions stimulated by his observations led him to explore the relevant scientific literature which he decodes for his readers. This is a book of biological discovery, a celebration of the capacity of living things to re-occupy a devastated location, and an encouragement for others to engage the natural world, even one that has been burnt to the ground."